Caracterização e Análise Funcional da Beta -1,3-glicanosiltransferase 2 de Paracoccidioides brasiliensis - LIMA, Patrícia de Sousa (2010)
Paracoccidioides brasiliensis is the causative agent of paracoccidioidomycosis (PCM), a systemic disorder geographically restricted to Central and South America, and one of the most important endemic mycoses in these regions, especially among the male rural populations. The disease is most likely caused by the inhalation of asexual spores (conidia) produced by the mycelia form of the fungus, propagules that once in the lungs undergo differentiation towards the parasitic yeast form. The cell wall of P. brasiliensis is a dynamic structure, essentially composed of branched glucan (β-1,3 and β-1,6 glucans), chitin, lipids and mannoproteins. Many enzymes are responsible for cell wall remodeling. One of them is the Beta-1,3- glucanosyltransferase 2 (PbGel2p) presented here. The amino acid deduced sequence of PbGel2p presented similarity to others proteins involved in fungal cell wall biosynthesis and morphogenesis and it was characterized as a member of GH72 family, GH72_ subfamily. The recombinant rPbGel2p was overexpressed in Escherichia coli and the polyclonal antibody was obtained. The PbGel2p mRNA, as well as the protein, were detected at the highest level in the mycelium phase. The potencial role of PbGel2p in cell wall biosynthesis and morphogenesis was analyzed by assessing its ability to rescue the phenotype of the Saccharomyces cerevisiae GAS1Δ. The results indicated that PbGel2p is a cell wall-associated protein that probably works as a β-1,3-glucan elongase capable of mediating fungal cell wall integrity. In addition, predicted protein-protein interactions between PbGel2p and others proteins of the fungus P. brasiliensis were assessed by using a S. cerevisiae two hybrid system and pull-down assay. The proteins that were found to interact with PbGel2p are: anthranilate synthase component 2 (involved in the tryptophan pathway), MYND domain protein SamB (related to fungal morphogenesis), mitotic spindle checkpoint protein Mad2B (required of the organization of the cytoskeleton and control of cell cycle), G protein complex beta subunit CpcB (organize the cytoskeleton of actin), WD repeat protein (involved in the control of cell cycle), phosphatidylinositol-4-phosphate-5-kinase its3 (required of the organization of the actin cytoskeleton), Hsp60 (related of stress conditions like temperature) and ATPase (localized in the plasma membrane / involved in the glucose metabolism). This suggested the relation of PbGel2p in other process to maintenance of cell wall integrity.